Design and Methods of the Pan-Canadian Applying Biomarkers to Minimize Long-Term Effects of Childhood/Adolescent Cancer Treatment (ABLE) Nephrotoxicity Study: A Prospective Observational Cohort Study. Issue 1 (16th February 2017) - McMahon, Kelly R.; Rod Rassekh, Shahrad; Schultz, Kirk R.; Pinsk, Maury; Blydt-Hansen, Tom; Mammen, Cherry; Tsuyuki, Ross T.; Devarajan, Prasad; Cuvelier, Geoff D. E.; Mitchell, Lesley G.; Baruchel, Sylvain; Palijan, Ana; et al.
Background: Childhood cancer survivors experience adverse drug events leading to lifelong health issues. The Applying Biomarkers to Minimize Long-Term Effects of Childhood/Adolescent Cancer Treatment (ABLE) team was established to validate and apply biomarkers of cancer treatment effects, with a goal of identifying children at high risk of developing cancer treatment complications associated with thrombosis, graft-versus-host disease, hearing loss, and kidney damage. Cisplatin is a chemotherapy well known to cause acute and chronic nephrotoxicity. Data on biomarkers of acute kidney injury (AKI) and late renal outcomes in children treated with cisplatin are limited. Objective: To describe the design and methods of the pan-Canadian ABLE Nephrotoxicity study, which aims to evaluate urine biomarkers (neutrophil gelatinase–associated lipocalin [NGAL] and kidney injury molecule-1 [KIM-1]) for AKI diagnosis, and determine whether they predict risk of long-term renal outcomes (chronic kidney disease [CKD], hypertension). Design: This is a 3-year observational prospective cohort study. Setting: The study includes 12 Canadian pediatric oncology centers. Patients: The target recruitment goal is 150 patients aged less than 18 years receiving cisplatin. Exclusion criteria : Patients with an estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2 or a pre-existing renal transplantation at baseline. Measurements: Serum creatinine (SCr), urine NGAL, and KIM-1 are measured during cisplatin infusion episodes (pre-infusion, immediate post-infusion, discharge sampling). At follow-up visits, eGFR, microalbuminuria, and blood pressure are measured and outcomes are collected. Methods: Outcomes: AKI is defined as per SCr criteria of the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. CKD is defined as eGFR <90 mL/min/1.73m2 or albumin-to-creatinine ratio≥3mg/mmol. Hypertension is defined as per guidelines. Procedure: Patients are recruited before their first or second cisplatin cycle. Participants are evaluated during 2 cisplatin infusion episodes (AKI biomarker validation) and at 3, 12, and 36 months post-cisplatin treatment (late outcomes). Limitations: The study has a relatively moderate sample size and short follow-up duration. There is potential for variability in data collection since multiple sites are involved. Conclusions: ABLE will provide a national platform to study biomarkers of late cancer treatment complications. The Nephrotoxicity study is a novel study of AKI biomarkers in children treated with cisplatin that will greatly inform on late cisplatin renal outcomes and follow-up needs.